2013
DOI: 10.5130/ajceb.v13i3.3300
|View full text |Cite
|
Sign up to set email alerts
|

The roles of emotional intelligence, interpersonal skill, and transformational leadership on improving construction safety performance

Abstract: Due to the characteristics of the construction industry, human skills are essential for working with and through others in managing safety. Previous research has shown that emotional intelligence, interpersonal skill, and transformational leadership are human skill components that generate superior performance in today's workplace. The aim of this research is to investigate the influence of project management personnel's human skills (in terms of emotional intelligence, interpersonal skill and transformational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 38 publications
2
28
0
7
Order By: Relevance
“…According to Fineman [48] and Joseph et al [49], many human resource managers in different companies around the globe use emotional intelligence-based assessments in the selection of new employees. This approach has been widely embraced by many organisations as a result of the numerous findings that relate safety performance to emotional intelligence [50][51][52]. Contrastingly, the model developed by this study shows that not all safety performance factors are affected by emotional intelligence.…”
Section: Discussionmentioning
confidence: 64%
“…According to Fineman [48] and Joseph et al [49], many human resource managers in different companies around the globe use emotional intelligence-based assessments in the selection of new employees. This approach has been widely embraced by many organisations as a result of the numerous findings that relate safety performance to emotional intelligence [50][51][52]. Contrastingly, the model developed by this study shows that not all safety performance factors are affected by emotional intelligence.…”
Section: Discussionmentioning
confidence: 64%
“…Responses were generated on a five-point Likert scale ranging from 1: strongly disagree to 5: strongly agree. The GTL scale has reported acceptable reliability in numerous studies including TFL assessment in construction projects (Carless et al, 2000;Sunindijo and Zou, 2013). The seven-item scale of TFL was coded as TFL1-TFL7, respectively, for the statistical assessments in PLS-SEM.…”
Section: Instrumentsmentioning
confidence: 99%
“…It was suggested that a 'differentiated lens' should be applied when examining the function of EI in a specific organizational context such as construction environment (Lindebaum and Cassell 2012). Taking a closer look at the dimensions of EI, Sunindijo and Zou (2013) found that self and relationship management are necessary in performing safety management tasks, while transformational leadership does not influence the performance of such tasks. This view is analogous to that of Tixier et al (2014) who discovered that project participants with a positive and neutral emotional state may be more likely to take more risks than those with a negative emotional state.…”
Section: Insert Table 2 Here a Review Of Ei In The Construction Industrymentioning
confidence: 99%